(untitled) (Research, Society and Development, 2022)
Sweets in paste and in pieces are considered products that help the development of the regions that produce them and are a good way of using and conserving the fruit. However, the scientific literature regarding the addition of probiotics in sweets is very scarce. The objective was to develop a functional creamy candy from the juazeiro fruit with the addition of fructooligosaccharide (FOS) and to explore its physicochemical and nutritional characteristics. Two formulations of creamy sweets were developed: DJP (control) containing only pulp, sucrose (60%) and lemon juice; and DJ1 containing pulp, sucrose (30%), FOS (10%) and lemon juice. The products were evaluated for physical-chemical and nutritional characterization. The moisture, ash, crude fiber, lipid and protein contents were higher (p<0.05) in the sweets plus FOS (38.4%; 1.11%; 1.72%; 0.05% and 1, 22% respectively). The pH, titratable acidity, Brixº, carbohydrates and total calories were higher (p<0.05) for the sweet control without FOS (5.03; 55.3º; 96.9% and 390.62 Kcal/100g, respectively). Phenolic compounds were superior in DJ1, while antioxidant activity did not differ significantly (p < 0.05). The formulations showed appropriate physicochemical and nutritional characteristics for their use, highlighting the bioactive compounds and fibers. The experimental candy proved to be a functional and innovative option.